Assessment of retinal nerve fiber layer thickness in migraine patients measured with optical coherence tomography - Khosravi, Alireza; Shahraki, Kourosh; Moghaddam, Afsaneh (International Journal of Advances in Medicine, 2018)
Background: Headache is one of the most disturbing symptoms with common neurological signs. Variations in optic nerve perfusion quality or retinal microcirculation may end up in peripapillary retinal nerve fiber layer (RNFL) thickness in patients with migraine. The aim of this study was to investigate the retinal nerve fiber layer (RNFL) thickness in patients with migraine. Methods: This cross-sectional study was conducted by including thirty patients diagnosed with migraine and thirty normal individuals. Patients were evaluated in groups including migraine with and without aura and controls. Retinal nerve fiber layer (RNFL) thickness was measured using stratus optical coherence tomography (OCT) and then was compared in case and control groups. All data were analyzed using SPSS software version 16. Results: RNFL thickness was significantly thinner in migraine patients compared to the control group. Symmetricity of RNFL showed significantly reduction in patients with migraine compared to standard value (95% vs 68%). Comparison of NRR area between patients and standard value showed significantly reduced values (P=0.0001). Mean value of optic disc area showed significantly reduced value compared to standard value about 2.35 m2 (P=0.0001). Conclusions: This study suggests that migraine leads to a reduction in the peripapillary RNFL thickness and to thinning in choroidal structures. These findings can be explained by a chronic ischemic insult related to migraine pathogenic mechanisms.